What construct one’s familiar area? A quantitative and longitudinal study - Zhang, Wen; Ahmad Termida, Nursitihazlin; Susilo, Yusak O (SAGE, 2017)
There is a lack of understanding of how certain characteristics of the urban environment influence an individual’s spatial cognition and familiarity with surrounding areas, and, subsequently, their travel behaviours and how these change over time. This paper aims to address this research gap in exploring the dynamics of individuals’ spatial cognitions by observing the changes of respondents’ familiar areas over time, and investigating the possible determinants that constitute respondents’ familiar areas. Panel data, containing two-week travel diaries and maps of familiar areas, were collected in four different waves over a seven-month period for 55 individuals in Stockholm, Sweden. The reported familiar areas for each individual were digitised into quantifiable variable form and further analysed by applying dynamic binary probit and linear regression models. The results show that, while familiar area is largely influenced by one’s previous knowledge of the area, it is also continuously corrected by events in between. Different land use characteristics have different impacts on different social groups’ travel patterns, thus contributing to the variability in the size of one’s familiar areas.